(untitled) (Medico Legal Update, 2020)
Hydatidosis is one of the most common parasitic zoonosis diseases not only in Iraq but throughout the world. Liver infected with hydatid cysts were randomly collected from 15 sheep and 18 cows of different ages and sexes during the period extended from September 2018 to December 2018. This study was aimed to provide insight on the histological changes of liver associated with E. granulosus and to compare the changes of liver tissue between sheep and cattle. Samples were collected from private (individual) butchers’ places at Diyala province in Iraq. Livers had been transferred to Zoology Laboratory in Department of Biology in College of Education for Pure Sciences in Diyala University. Specimens from infected livers were immediately taken and fixed in 10 % formalin. Then the routine histological sections were done. The results showed that there were many histological changes resulting from infection with hydatid cysts infection including infiltration of inflammatory cells, necrosis, degeneration of liver tissue, fibrosis, fibrosis around portal veins, congestion of portal vein, increase in bile duct numbers, maladjustment of hepatic cords. A comparison between the histological changes of sheep and cattle showed the same histological changes, with a difference in the severity of these changes as they were more severe and developed in the livers of cattle than in sheep.